Coffee in the Russian literature of the 18th and early 19th centuries - Stankeviciene, Anastasija (Vilnius University Open Series, 2024)
In the article, coffee is analyzed as one of the aspects of the cultural code of the Russian society in the 18th century. The historical context of the adaptation of coffee in Russia is also reconstructed. The purpose of the research is to reveal the semantic features of coffee in the texts of Russian authors of the 18th – early 19th centuries. Through semantic and comparative analysis of the coffee theme in the texts of A. Kantemir, G. Derzhavin, Catherine II, I. Krylov, V. Kuchelbecker and others, the range of meanings of the beverage and the context of using the word coffee is determined: from a negative attribute of the aristocracy to a positive ‘inspiration elixir’. The connections between coffee and the social status of the character are also investigated.
Keywords: coffee; Russian literature; 18th century